إدارة قرارات الائتمان في البنوك التجارية وأثرها علي ربحية البنوك: ) دراسة حالة بنك البركة - فرع النيل الابيض - كوستي (2024م) - د. احمد عبد الرحمن عمر, (White Nile Journal for Studies and Research, 2024)
The study examined the management of credit decisions in commercial banks and their impact on banks’ profitability. The problem of the study was how to manage banking risks. The study, Net Group, assumed the most important hypotheses: that legislation and laws issued by the Central Bank of Sudan and commercial banks to adapt to the Basel Committee standards still require deep financial reforms to protect against the financial risks resulting from the credit process. The study relied on the descriptive analytical approach and the statistical approach. The study reached several results, the most important of which are: that the recommendations of the Basel Committees found acceptance and approval from most international and local financial and banking institutions, and this is what was made clear by the answers of the respondents, and that the internal financial and monetary policies influenced the recommendations of the Basel Financial Committees. The study made recommendations, the most important of which are: working to find new mechanisms and recommendations to reduce the remaining risks in global and local banking and providing risk management with modern mechanisms and aids to facilitate its tasks and achieve its goals.